Autism-Linked Mutations in α2δ-1 and α2δ-3 Reduce Protein Membrane Expression but Affect Neither Calcium Channels nor Trans-Synaptic Signaling - Sabrin Haddad; Manuel Hessenberger; Cornelia Ablinger; Clarissa Eibl; Ruslan Stanika; Marta Campiglio; Gerald J. Obermair (Pharmaceuticals)
Background: α2δ proteins regulate membrane trafficking and biophysical properties of voltage-gated calcium channels. Moreover, they modulate axonal wiring, synapse formation, and trans-synaptic signaling. Several rare missense variants in CACNA2D1 (coding for α2δ-1) and CACNA2D3 (coding for α2δ-3) genes were identified in patients with autism spectrum disorder (ASD). However, the pathogenicity of these variants is not known, and the molecular mechanism by which α2δ proteins may contribute to the pathophysiology of autism is, as of today, not understood. Therefore, in this study we functionally characterized two heterozygous missense variants in α2δ-1 (p.R351T) and α2δ-3 (p.A275T), previously identified in patients with ASD. Methods: Electrophysiological recordings in transfected tsA201 cells were used to study specific channel-dependent functions of mutated α2δ proteins. Membrane expression, presynaptic targeting, and trans-synaptic signaling of mutated α2δ proteins were studied upon expression in murine cultured hippocampal neurons. Results: Homologous expression of both mutated α2δ proteins revealed a strongly reduced membrane expression and synaptic localization compared to the corresponding wild type α2δ proteins. Moreover, the A275T mutation in α2δ-3 resulted in an altered glycosylation pattern upon heterologous expression. However, neither of the mutations compromised the biophysical properties of postsynaptic L-type (CaV1.2 and CaV1.3) and presynaptic P/Q-type (CaV2.1) channels when co-expressed in tsA201 cells. Furthermore, presynaptic expression of p.R351T in the α2δ-1 splice variant lacking exon 23 did not affect trans-synaptic signaling to postsynaptic GABAA receptors. Conclusions: Our data provide evidence that the pathophysiological mechanisms of ASD-causing mutations of α2δ proteins may not involve their classical channel-dependent and trans-synaptic functions. Alternatively, these mutations may induce subtle changes in synapse formation or neuronal network function, highlighting the need for future α2δ protein-linked disease models.